Students’ Perception on Hybrid Learning in ELT in the New Normal Era - Ika Sartika; Nur Aeni; Hasriani G. (State University of Makassar, 2024)
This study aims to explore students’ perceptions of hybrid learning in ELT in the new normal era. The researcher applies a qualitative method. To achieve the research objectives, the researcher used an instrument namely interviews. The class of 2021 English Education students from Universitas Negeri Makassar's Faculty of Languages and Literature make up the research's population.The class of 2021 English Education students from Universitas Negeri Makassar's Faculty of Languages and Literature make up the research's population.The sample of this interview was 20 students from class E (class SL). The researcher interviewed 13 students via online and 7 students through face-to-face interviews using taken semi-structured interview technique. According to the data analysis results, most students had a positive opinion of hybrid learning in ELT. The respondents' positive statements about the approach were based on their own experiences learning through it. The result of hybrid learning was very flexible to use, efficient for learning, helpful to learn and increasing their skill technology and motivation. Negative opinions about the students' struggles with hybrid learning were also discovered, as a result of their lack of internet access and inability to comprehend the subject matter. Keywords— Students’ perception, Hybrid Learning, English Learning Teaching